1997
DOI: 10.1104/pp.115.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cDNA Clones Encoding Sucrose-Phosphate Synthase in Relation to Sugar Interconversions Associated with Dehydration in the Resurrection Plant Craterostigma plantagineum Hochst

Abstract: Sucrose-phosphate synthase (SPS) is a key enzyme in the regulation of sucrose metabolism, being responsible for the synthesis of sucrose 6-phosphate from fructose 6-phosphate and uridine 5 ' -diphosphate-glucose. W e report on the isolation and characterization of cDNA clones encoding SPS from Craferosfigma planfagineum Hochst., a resurrection plant in which the accumulation of sucrose is considered to play an important role in tolerance to severe protoplastic dehydration. Two distinct classes of cDNAs encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 39 publications
(58 reference statements)
2
32
1
Order By: Relevance
“…A similar expression pattern has been reported for a member of the rice (Oryza sativa) SPS B family that was highly expressed in immature inflorescences, and it has been proposed that in rice the SPS B isoform might be involved in the supply of carbon to developing pollen grains (Chávez-Bárcenas et al, 2000). Expression of the B isoform seems to be induced by stress-related environmental factors in kiwi (Actinidia deliciosa; Fung et al, 2003) and in C. plantagineum (Ingram et al, 1997), however, it is currently not known whether this holds also true for NtSPSB.…”
Section: Sps Gene Families Are Differentially Expressed In Tobaccomentioning
confidence: 99%
See 1 more Smart Citation
“…A similar expression pattern has been reported for a member of the rice (Oryza sativa) SPS B family that was highly expressed in immature inflorescences, and it has been proposed that in rice the SPS B isoform might be involved in the supply of carbon to developing pollen grains (Chávez-Bárcenas et al, 2000). Expression of the B isoform seems to be induced by stress-related environmental factors in kiwi (Actinidia deliciosa; Fung et al, 2003) and in C. plantagineum (Ingram et al, 1997), however, it is currently not known whether this holds also true for NtSPSB.…”
Section: Sps Gene Families Are Differentially Expressed In Tobaccomentioning
confidence: 99%
“…Total (dpm) 6,518 6 1,855 5,339 6 1,445 5,181 6 1,573 8,374 6 2,087 8,913 6 3,079 Insoluble 39.2 6 3.5 42.1 6 4.1 42.7 6 3.8 41.3 6 3.5 42.5 6 5.2 Soluble 60.8 6 3.5 57.9 6 4.1 57.3 6 3.8 58.7 6 3.5 57.5 6 5.2 Neutral 46.7 6 4.6 48.7 6 9.5 41.6 6 8.0 41.9 6 4.3 40.6 6 14.4 Anionic 8.7 6 3.8 8.2 6 2.0 9.9 6 3.8 7.4 6 0.5 7.8 6 2.9 Cationic 6.9 6 0.7 8.8 6 1.4 9.1 6 0.6 8.1 6 0.8 7.9 6 0.7 1997), citrus (Komatsu et al, 1996), Oncidium goldiana (Li et al, 2003), and Craterostigma plantagineum (Ingram et al, 1997). All regulatory phosphorylation sites known for SPS are well conserved among A-family members from different species (Langenkämper et al, 2002).…”
Section: Sps Gene Families Are Differentially Expressed In Tobaccomentioning
confidence: 99%
“…C. plantagineum possesses a set of genes encoding isoenzymes of Suc synthase and Suc phosphate synthase (Ingram et al, 1997;Kleines et al, 1999), which are differentially expressed. Besides these enzymes and the dehydration-induced expression of cytosolic glyceraldehyde dehydrogenase, it has been proposed that transketolase contributes to the conversion of octulose to Suc.…”
Section: Carbohydrate Metabolismmentioning
confidence: 99%
“…Xu et al (1996) used the microprojectile bombardment method to transfer a barley late embryogenesis abundant (LEA) gene into rice and detected a significant increase in LEA protein as well as obviously improved rice drought tolerance, which suggested that the LEA protein could protect rice against drought stress-related injury. In the presence of the overexpression of P5CS and δ-OAT, two key genes involved in the proline biosynthesis process, proline content was increased and rice drought resistance was significantly enhanced (Ingram et al, 1997;Wu et al, 2003). Igarashi et al (1997) isolated P5C cDNA (cosP5CS) from Akibare and found that P5CS could be induced by all stress factors including drought.…”
Section: Introductionmentioning
confidence: 99%